Community acquired urinary tract infection in pediatric age-group with changing trends of antibiotic resistance pattern over 3 years: a clinico-epidemiological study - Chakroborty, Baishali; Dutta, Sumanta Kumar; Chaudhuri, Patralekha Ray; Santra(Dhali), Ranjita (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Assessment of the antimicrobial sensitivity pattern in urinary isolates of the children suffering from urinary tract infection (UTI) and evaluation of the recent trends of multi-drug resistance in the isolates. The aim was to find out the antibiotics sensitivity of the organisms isolated from the urine samples of pediatric age-group with emphasis on their resistance pattern. Methods: A clinico-epidemiological study comprising of 304 specimens of urine were collected among all the children with UTI below 12 years of age, attending pediatric outpatient department of a tertiary care teaching hospital in eastern India wet mount microscopy and semi quantitative culture were done to diagnose UTI. Organisms isolated were identified by standard biochemical tests, and antibiogram studies were done by standard Kirby-Bauer disc diffusion test statistical analysis, Microsoft excel and SPSS were used for analysis of data. Results: Aminoglycosides had wider sensitivity pattern toward most of the uropathogens whereas tetracyclines and co-amoxyclav in particular were resistant for most of the organisms. Among all the organisms, Pseudomonas and Enterococcus species showed higher resistance pattern toward the conventional antimicrobials. Conclusions: The changing trends in the anti-biograms of several Gram-positive and Gram-negative microorganisms in UTI demands reconsideration with respect to rational drug use in the pediatric age group.